Is CSF1R Expression Localization Crucial for its Prognostic Value in Colorectal Cancer?. Issue 1 (January 2021) - Guan, Huiyuan; Wang, Xin; Song, Yongxi; Gao, Peng; Li, Yuan; Wu, Zhonghua; Zhu, Jinliang; Wang, Zhenning
Abstract : The colony-stimulating factor 1 receptor (CSF1R) is commonly known as a transmembrane receptor on tumor-associated macrophages, which are essential in the tumor microenvironment. However, the expression pattern and prognosis of CSF1R are still unknown in colorectal cancer (CRC) and are still controversial among various cancers. To clarify the expression pattern and prognosis of CSF1R in CRC, we performed immunohistochemistry on 332 CRC tissue and 283 nontumorous adjacent tissues. We explored the expression pattern of CSF1R and analyzed its relationship with clinical characteristics and prognosis. The positive expression ratio of CSF1R was much higher in nontumorous adjacent tissues, while the positive cytomembrane ratio of CSF1R was much higher in cancer tissue. Furthermore, we found that CSF1R expression, especially in the cytoplasm, acted as a protective factor. However, our findings indicated that CSF1R expression on the cytomembrane decreased its prognostic predictive value. These results emphasize the important role of the localization of CSF1R and may also explain the contrasting effects seen between various cancers.